ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT. PANCA MITRA MULTI PERDANA - Anik Sudarismiati; Zainuddin Zainuddin (Relawan Jurnal Indonesia, 2018)
The current economy has grown rapidly, along with the rapidly increasing development of Science and Technology (IPTEK). So the competition between companies becomes increasingly tight. The increasingly tight competition between companies encourages every company to establish control of raw material inventory appropriately so that the company can still exist to be able to achieve the desired goals. In doing this research method used is Interview, Library study, Documentation, and Observation at PT. Panca Mitra Multi Perdana. The data analysis technique used is EOQ formula to know optimal buying level, and total cost of raw material inventory by TIC method (Total Inventory Cost), calculate safety stock and Reorder (Reoder point). After going through various discussions or analyzes that have been done in the chapter in advance, from beginning to end, then from the results of the analysis can be concluded as follows: Economic Purchase by PT Panca Mitra Multi Perdana that is 79.765 Kg of shrimp with frequency of purchase for one year (2016) 180 times with a minimal cost of Rp. 1.123.000. Planning and control of raw material inventory can launch production process and minimize cost, because if not known production plan year 2016 (9,574,829 Kg), hence requirement of raw material (9,574,829 Kg.) Also unknowable causing disruption of production process, and of course also can not be determined how much economic purchases (79,765 Kg Per order) resulting in too high costs to be incurred.